2021
DOI: 10.2486/indhealth.2020-0251
|View full text |Cite
|
Sign up to set email alerts
|

The relationship among sleep reactivity, job-related stress, and subjective cognitive dysfunction: a cross-sectional study using path analysis

Abstract: Insomnia, job-related stress, and cognitive dysfunction affect the mental health of workers. However, the relationships among sleep reactivity, jobrelated stress, and subjective cognitive dysfunction in workers remains not fully understood. Therefore, this study seeks to investigate the relationships among these variables in Japanese adult workers. In total, 536 adult workers in Japan were evaluated using the Japanese version of Ford Insomnia Response to Stress Test, Brief Job Stress Questionnaire, and Cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Adequate sleep and reasonable stress relief are considered indispensable elements of health, general wellbeing, and proper daily functioning. Stress and insomnia might reduce clinicians' QOL by leading to cognitive dysfunction ( 60 ), physical discomfort ( 61 ), and job burnout ( 62 ). Further studies on the sleep patterns and stress management strategies of young front-line clinicians in high-risk areas are needed to develop strategies to prevent or alleviate problems and improve the QOL.…”
Section: Discussionmentioning
confidence: 99%
“…Adequate sleep and reasonable stress relief are considered indispensable elements of health, general wellbeing, and proper daily functioning. Stress and insomnia might reduce clinicians' QOL by leading to cognitive dysfunction ( 60 ), physical discomfort ( 61 ), and job burnout ( 62 ). Further studies on the sleep patterns and stress management strategies of young front-line clinicians in high-risk areas are needed to develop strategies to prevent or alleviate problems and improve the QOL.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep reactivity, i.e., the extent of which sleep disruption occurs due to stress exposure, is another element of sleep satisfaction where difficulty of falling and staying asleep are affected [43]. A recent cross-sectional study, which also implemented the BJSQ, concluded that sleep reactivity could affect occupational stress, specifically stress reaction [44]. Conversely, there is a consensus that stress disrupts sleep on multiple levels, including sleep efficiency and sleep depth [45].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, sleep/insomnia/circadian rhythm (n = 11) were frequently investigated for their association with job stressors. Toyoshima et al [55] examined interrelationships among sleep reactivity, job-related stress, and subjective cognitive dysfunction and indicated that sleep reactivity significantly influenced subjective cognitive dysfunction directly and indirectly via job stressors and stress responses. Takahashi et al [46] conducted a one-year longitudinal study to examine how a change in work time control was associated with sleep and health.…”
Section: Used Subscales and Other Measurementsmentioning
confidence: 99%